2021
DOI: 10.1186/s12935-021-02012-9
|View full text |Cite
|
Sign up to set email alerts
|

RSF1 in cancer: interactions and functions

Abstract: RSF1, remodelling and spacing factor 1, is an important interphase centromere protein and is overexpressed in many types of cancers and correlated with poor overall survival. RSF1 has functions mainly in maintaining chromosome stability, facilitating DNA repair, maintaining the protein homeostasis of RSF1 and suppressing the transcription of some oncogenes when RSF1 protein is expressed at an optimal level; however, RSF1 overexpression facilitates drug resistance and cell cycle checkpoint inhibition to prompt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…1d - f ). Further TCGA analysis revealed that both invasive BRCA, including its deadly subtype, triple negative breast cancer (TNBC), and metastatic BRCA, displayed gene amplification and expressed significantly higher levels of RNF2 and RSF1 , which are overexpressed and associated with poor patient prognosis in various other types of cancers 30 , compared to normal controls at both transcriptional and protein levels ( Extended Data Fig. 2a - e ).…”
Section: Resultsmentioning
confidence: 99%
“…1d - f ). Further TCGA analysis revealed that both invasive BRCA, including its deadly subtype, triple negative breast cancer (TNBC), and metastatic BRCA, displayed gene amplification and expressed significantly higher levels of RNF2 and RSF1 , which are overexpressed and associated with poor patient prognosis in various other types of cancers 30 , compared to normal controls at both transcriptional and protein levels ( Extended Data Fig. 2a - e ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that these genes are involved in various biological processes of tumour cells. For example, overexpression of remodelling and spacing Factor 1 Frontiers in Genetics frontiersin.org 13 (RSF1) has been reported to promote the proliferation and survival of tumour cells (Cai et al, 2021); RE1-silencing transcription factor (REST) was reported to regulate cell apoptosis, the cell cycle, cell proliferation, metastasis, invasion and tumorigenesis (Taghvaei et al, 2021); As a tumour promoter, STRN is upregulated in HCC (Du et al, 2020); and Rap1-interacting Factor 1 (RIF1) expression was found to be significantly correlated with clinical stage and prognosis. Our results showed for the first time that there are significant correlations of RNF169 with the expression of RSF1, REST, STRN and RIF1 in PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Two major hits, Smarca5 and Baz1b, are part of the ISWI family of chromatin remodeling factors, together forming, among others, the WSTF-IS-WI chromatin remodeling complex (WICH) complex that facilitates DNA replication and chromatin maturation and promotes DNA repair (40)(41)(42). Smarca5 together with RSF1 also forms the remodeling and spacing factor (RSF) complex, which is involved in transcriptional regulation and promotion of DNA repair (43). RSF1 was also identified in our Uhrf2 interaction screen, suggesting that Uhrf2 is part of this complex and affects gene transcription.…”
Section: Discussionmentioning
confidence: 99%